Enhancement of thermoelectric properties in p-type ZnSb alloys through Cu-doping - Dharmaiah, Peyala; Heo, Minsu; Nagarjuna, Cheenepalli; Jung, Sung Jin; Won, Sung Ok; Lee, Kyu Hyoung; Kim, Seong Keun; Kim, Jin Sang; Ahn, Byungmin; Kim, Hyun Sik; Baek, Seung Hyub (Journal of Alloys and Compounds, 2024)
To meet the growing demand for thermoelectric devices operating in intermediate temperature ranges, it is essential to develop high-performance materials with superior thermoelectric properties and robust mechanical strength. In this study, we systematically optimized carrier concentration by introducing acceptor impurities into ZnSb materials. Our results demonstrate that doping Cu into the Zn site effectively modulates hole carrier concentration, leading to a substantial enhancement in electrical conductivity and a remarkable improvement in power factor (107 %). Consequently, we achieved a high peak ZT of 1.04 at 600 K and an average ZTave value of 0.63 within the temperature range of 300–600 K. This yielded a calculated efficiency of ηmax = 7 % at ΔT = 300 K, for the Zn0.99Cu0.01Sb sample, which is 134 % higher than that of the pristine ZnSb sample (ηmax = 2.98 %). Moreover, the superior hardness and fracture toughness (KIC) of ZnSb samples compared to other state-of-the-art thermoelectric materials make them highly desirable for real-time applications.
Keywords: Charge carrier concentration optimization; Charge carrier concentrations; Mechanical performance; Optimisations; Power factors; Temperature range; Thermo-Electric materials; Thermoelectric material; Thermoelectric properties; Znsb alloy; Charge carrier concentration optimization; Mechanical performance; Power factor; Thermoelectric materials; ZnSb alloys